Design and study protocol of the maternal smoking cessation during pregnancy study, (M-SCOPE) - Loukopoulou Andriani N; Vardavas Constantine I; Farmakides George; Rossolymos Christos; Chrelias Charalambos; Tzatzarakis Manolis N; Tsatsakis Aristidis; Lymberi Maria; Connolly Gregory N; Behrakis Panagiotis K (BMC, 2011)
Abstract Background Maternal smoking is the most significant cause of preventable complications during pregnancy, with smoking cessation during pregnancy shown to increase birth weight and reduce preterm birth among pregnant women who quit smoking. Taking into account the fact that the number of women who smoke in Greece has increased steadily throughout the previous decade and that the prevalence of smoking among Greek females is one of the highest in the world, smoking cessation should be a top priority among Greek health care professionals. Methods/Design The Maternal Smoking Cessation during Pregnancy Study (M-SCOPE), is a Randomized Control Trial (RCT) that aims to test whether offering Greek pregnant smokers a high intensity intervention increases smoking cessation during the third trimester of pregnancy, when compared to a low intensity intervention. Prospective participants will be pregnant smokers of more than 5 cigarettes per week, recruited up to the second trimester of pregnancy. Urine samples for biomarker analysis of cotinine will be collected at three time points: at baseline, at around the 32nd week of gestation and at six months post partum. The control group/low intensity intervention will include: brief advice for 5 minutes and a short leaflet, while the experimental group/intensive intervention will include: 30 minutes of individualized cognitive-behavioural intervention provided by a trained health professional and a self-help manual especially tailored for smoking cessation during pregnancy, while counselling will be based on the ''5 As.'' After childbirth, the infants' birth weight, gestational age and any other health related complications during pregnancy will be recorded. A six months post-partum a follow up will be performed in order to re-assess the quitters smoking status. Discussion If offering pregnant smokers a high intensity intervention for smoking cessation increases the rate of smoking cessation in comparison to a usual care low intensity intervention in Greek pregnant smokers, such a scheme if beneficial could be implemented successfully within clinical practice in Greece. Trial Registration ClinicalTrials.gov Identifier NCT01210118